Biliary ileus: X-ray visualization of the cholecystoduodenal fistula - Liard, Washington; Boix, Enrique (Cirugía del Uruguay, 2020)
A case of gallstone intestinal obstruction is reported. Roentgenologic study by means of a barium meal showed the type of the bilioenteric fistula